The trust factor : the science of creating high-performance companies - Zak, Paul J. (AMACOM, 2017)
Why is "culture" so difficult to improve? What makes so many good employees check out? Neuroscientist Paul Zak shows that innate brain functions hold the answers. It all boils down to trust. When someone shows you trust, a feel-good jolt of oxytocin surges through your brain and triggers you to reciprocate. This simple mechanism creates a perpetual trust-building cycle-the key to changing stubborn workplace patterns. Drawing on his original research, Zak teases out science-backed insights for building high-trust organizations. Trust Factor opens a window on how brain chemicals affect behavior,